Startup Transient Characteristics of Helical Grooved Flat Heat Pipe - Kumar Sridharan, Kesav; S. Nagappa, Sridhara; Y. Paralikar, Siddarth (International Journal of Engineering and Technology, 2018)
Heat pipes are used in thermal management of electronic devices due to their efficient heat transfer capability from source to sink with a very small temperature difference. These passive heat transfer devices can employ sintered powder, screen mesh, machined grooves or its combination as wick material to exert capillary action on the working fluid. In this work, attempt was made to develop a flat heat pipe using a helical grooved cylindrical pipe. The helical groove present in the cylindrical pipe is used as wick. The developed flat heat pipe was targeted for a power range of 3 W without dedicated cooling mechanism for condenser. Experimental studies were also conducted up to 5 W to verify the extension of operating power range of the heat pipe using a fan. Â This paper primarily focus on the transient behavior of to understand the time constant of the heat pipe at different orientations and cooling scenarios. Later the transient thermal performance of heat pipe was also compared with dry heat pipe.Â